Mycobacterium tuberculosis phylogeography in the context of human migration and pathogen's pathobiology: Insights from Beijing and Ural families. (June 2015) - Mokrousov, Igor
Summary: Here, I review the population structure and phylogeography of the two contrasting families of Mycobacterium tuberculosis, Beijing and Ural, in the context of strain pathobiology and human history and migration. Proprietary database (12-loci MIRU-VNTR profiles of 3067 Beijing genotype isolates) was subjected to phylogenetic and statistical analysis. The highest rate (90%) and diversity (HGI 0.80–0.95) of the Beijing genotype in North China suggest it to be its area of origin. Under VNTR-based MDS analysis the interpopulation genetic distances correlated with geography over uninterrupted landmasses. In contrast, large water distances together with long time generated remarkable outliers. Weak and less expected affinities of the distant M . tuberculosis populations may reflect hidden epidemiological links due to unknown migration. Association with drug-resistance or increased virulence/transmissibility along with particular human migration flows shape global dissemination of some Beijing clones. The paucity of data on the Ural genotype prevents from high-resolution analysis that was mainly based on the available spoligotyping data. The North/East Pontic area marked with the highest prevalence of the Ural family may have been the area of its origin and primary dispersal in Eurasia. Ural strains are not marked by increased pathogenic capacities, increased transmissibility and association with drug resistance (but most recent reports describe an alarming increase of MDR Ural strains in some parts of eastern Europe and northwestern Russia). Large-scale SNP or WGS population-based studies targeting strains from indigenous populations and, eventually, analysis of ancient DNA will better test these hypotheses. Host genetics factors likely play the most prominent role in differential dissemination of particular M . tuberculosis genotypes.